The Impact of ESG Performance on Corporate Financial Performance--The Moderating Effect of Digital Level - Teng , Shunping; Ibrahim, Haslindar; Chen, Meng; Wang, Xiaoran (Business Management and Strategy, 2024)
In response to economic development, companies are striving to improve their financial performance in order to seek long-term growth and development. As a major player in market economic activities, corporations are constantly undergoing digital transformation. Its qualities of technology, innovation, intelligence and uniqueness can enable companies to gain new competitive advantages and gradually become one of the important factors influencing ESG practices. The current study examines how ESG performance affects corporate financial performance using a two-way fixed-effects method employing a moderating effects framework. This study uses panel data from listed companies on the Shanghai and Shenzhen stock exchanges between 2014 and 2022 to investigate whether ESG performance could enhance corporate financial performance. The statistical results show that, the impact of ESG performance on corporate financial performance is moderated by three dimensions of digital level. Digital strategy, digital investment and digital staff all have significant, beneficial moderating effect on the relationship between ESG performance and corporate financial performance. The study adds to the body of knowledge in ESG performance and corporate financial performance by providing insights into the moderating effect of digital level that improve their financial performance.